Whole-Genome Sequence of an Indian Group A Streptococcus emm Type 1-2 Strain Isolated from a Blood Sample in North India - Sagar, Vivek (Microbiol Resour Announc, 2020)
Group A Streptococcus emm type 1-2 is more prevalent than emm type 1 in India. Only partial information is available about the genetic characteristics of this type. Here, genome sequencing of emm type 1-2 strain 1085 (from blood) was conducted. A contig 2,010,300 bp long, with a total of 1,877 annotated proteins, was obtained (NCBI accession number CP047120, assembly accession number ASM983284v1).